Electrospinning of polymethyl methacrylate nanofibers: Optimization of processing parameters using the Taguchi design of experiments - Khanlou, H.M.; Ang, B.C.; Talebian, S.; Afifi, A.M.; Andriyana, A. (2015)
The effects of polymer concentration and electrospinning parameters on the diameter of electrospun polymethyl methacrylate (PMMA) fibers were experimentally investigated. It was also studied how the controlled factors would affect the output with the intention of finding the optimal electrospinning settings in order to obtain the smallest PMMA fiber diameter. Subsequently the solution feed rate, needle gauge diameter, supply voltage, polymer concentration and tip-to-collector distance were considered as the control factors. To achieve these aims, Taguchi's mixed-level parameter design (L-18) was employed for the experimental design. Optimal electrospinning conditions were determined using the signal-to-noise (S/N) ratio that was calculated from the electrospun PMMA fiber diameter according to the-smaller-the-better approach. Accordingly, the smallest fiber diameter observed was 228 (+/- 76) nm and it was yielded at 15wt polymer concentration, 20kV of supply voltage, 1ml/h feed rate, 15cm tip-to-distance and 19 needle gauge. Moreover, the S/N ratio response showed that the polymer concentration was the most effective parameter on determination of fiber diameter followed by feed rate, tip-to distance, needle gauge and voltage, respectively. The Taguchi design of experiments method has been found to be an effective approach to statistically optimize the critical parameters used in electrospinning so as to effectively tailor the resulting electrospun fiber diameters and morphology.